Take-Home-Naloxon in Deutschland (Nomos Verlagsgesellschaft mbH & Co. KG, 2025)
While Take-Home Naloxone (THN) is recognized as a lifesaver in countries like the USA and Canada, this harm reduction measure falls significantly short of its potential in Germany. This book provides an initial overview of THN, its distribution in Germany, and what would be needed to ensure nationwide access to prevent drug-related deaths. As part of the NALtrain project, staff from AIDS and drug support organizations were trained to offer naloxone training to people who use opioids. The book presents the project’s findings, derives recommendations for broader implementation, and lays the groundwork for advancing THN in Germany.